The hugging tree A story about resilience - Neimark, Jill (Magination Press, 2016)
The Hugging Tree tells the story of a little tree growing all alone on a cliff, by a vast and mighty sea. Through thundering storms and the cold of winter, the tree holds fast. Sustained by the natural world and the kindness and compassion of one little boy, eventually the tree grows until it can hold and shelter others. The resilience of the Hugging Tree calls to mind the potential in all of us; to thrive, despite times of struggle and difficulty. To nurture the little spark of hope and resolve. To dream and to grow, just where we are.